PERILAKU MEMINUM-MINUMAN KERAS DI KALANGAN REMAJA DI KELURAHAN SUNGAI SALAK KECAMATAN TEMPULING KABUPATEN INDRAGIRI HILIR - Agnes Siswendi; Basri " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Research background by teenagers who likes to deviant behavior, deviation is abehavior that is not in accordance with the values of decency. Deviant behavior here isbehavior-drinking liquor that is still happening in the Village of Bark River TempulingIndragiri Hilir subdistrict. This study aims to find out what the motive teen teens do andhow knowledge about the negative behavior.The benefits of research as educational material to the reader about what causedthe drinking behavior as well as information for those who want to continue researchrelated to the same problem. Source of the data obtained are qualitative, in the form ofprimary and secondary data. The method to determine the information used is the censusmethod, which is taken from the respondents, village head's office, the district office,police. Methods of analysis of data obtained deskiftip done qualitatively. The resultsshowed that adolescents motive liquor activities due to environmental factors, 13.3%,66.6% peer influence. Lack of knowledge about the impact of juvenile liquor itself andthe impact of liquor for individual health threat to the environment while will disturb thepublic tranquility where 23.3% extortion. Some of these factors have a major role tochange the mental attitude and the teens and surrounding communitiesKeywords: Teen, Motif, Deviant Behavior.